Nutritional Parameters and Their Genetic Variability in Bold Grained Rice (Oryza sativa L.) Genotypes of Assam - CHAKRABORTY, R.; CHAKRABORTY, S.; DUTTA, B.K.; PAUL, S.B. (Asian Journal of Chemistry, 2010)
In Barak valley zone of Assam the physically hard working people prefer bold grained rice with good taste because of slow digestion and longer retention in the stomach. But most of the modern high yielding rice varieties is medium and fine grained. Keeping the need of rural people in mind, the present experiment was conducted on 47 bold grained rice genotypes with two recommended high yielding check varieties namely Ranjit and Monohar Sali of Barak Valley, Assam. The mean performances of 8 nutritional parameters of these 49 genotypes were evaluated. Crude protein content (%), total soluble protein content (g/ 100 g of oven dry sample), the amino acids lysine content and tryptophan content (g/16 g of N) varied from 7.09 to 13.10, 4.10 to 6.69, 3.20 to 4.45 and 0.56 to 1.10, respectively. The ash content (%) and phosphorus content (%) varied from 0.88 to 1.50 and 0.213 to 0.430, respectively. Calcium and iron content (mg/100 g) ranged from 16.59 to 37.98 and 1.11 to 3.92, respectively in the bold grained rice genotypes. The difference between phenotypic (PCV) and genotypic (GCV) coefficient of variations was very small for all the above nutritional parameters indicating greater role of genetic factors in their expression. In the present investigation, high heritability associated with high genetic advance was found in the characters viz., calcium content and iron content. Breeding method based on progeny testing and mass selection could be useful in improving these traits. High heritability along with moderate genetic advance was observed in the characters crude protein content, total soluble protein content and ash content. Judicious application of pure line selection could be effective for improving these characters. Lastly high heritability with low genetic advance was recorded for the amino acids lysine and tryptophan content and phosphorus content. This indicated that these nutritional parameters were mostly governed by nonadditive gene action (dominance and epistasis) in their inheritance.